2020
DOI: 10.1016/j.jacc.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Myocardial Injury in Patients Hospitalized With COVID-19 Infection

Abstract: BACKGROUND The degree of myocardial injury, as reflected by troponin elevation, and associated outcomes among U.S. hospitalized patients with coronavirus disease-2019 (COVID-19) are unknown. OBJECTIVES The purpose of this study was to describe the degree of myocardial injury and associated outcomes in a large hospitalized cohort with laboratory-confirmed COVID-19.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
487
7
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 611 publications
(537 citation statements)
references
References 27 publications
28
487
7
15
Order By: Relevance
“…A larger retrospective study from New York not utilizing high-sensitivity assays showed that elevated troponin-I was associated with increased risk of death in a large US population. 21 Other studies have found that while inflammatory markers demonstrated correlation with ICU transfer or death, only CRP was found to be independently associated with these outcomes. 22 Our study population was larger and had much higher rates of cardiovascular risk factors and obesity.…”
Section: Discussionmentioning
confidence: 95%
“…A larger retrospective study from New York not utilizing high-sensitivity assays showed that elevated troponin-I was associated with increased risk of death in a large US population. 21 Other studies have found that while inflammatory markers demonstrated correlation with ICU transfer or death, only CRP was found to be independently associated with these outcomes. 22 Our study population was larger and had much higher rates of cardiovascular risk factors and obesity.…”
Section: Discussionmentioning
confidence: 95%
“…3−5 But a recent study from New York showed a similar prevalence of myocardial injury in hospitalized Covid-19 patients. 7 There is evidence to suggest acute myocardial injury at hospital admission is also associated with increased in-hospital mortality in Covid-19. 8 However, ours is the first study to demonstrate increased mortality with higher cTnI levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies, we found that patients with myocardial injury were older, had a higher prevalence of the cardiovascular disease, and had higher inflammatory markers. [3][4][5]7 Possible mechanisms of myocardial injury in Covid-19 include direct damage to the cardiomyocytes, systemic inflammation, myocardial interstitial fibrosis, interferon -mediated immune response, exaggerated cytokine response by Type 1 and 2 helper T cells, coronary plaque destabilization, oxygen supply-demand mismatch, microembolic infarcts, hyperadrenergic state, and pulmonary embolism. 9,10 Based on the Fourth Universal Definition of Myocardial Infarction, there were very few patients who met the strict criteria for acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…patients with elevated hs-cTnI levels [28][29], moreover, our ndings suggest that even when adjusted for in uences such as sex, age and disease history, hs-cTnI levels continued to work in predicting the progression of prognosis and the outcome of death in serious cases. As a result, early monitoring of cardiac injury-related markers, including hs-cTnI, can play a signi cant role in reducing the risk of death in serious condition.…”
Section: Discussionmentioning
confidence: 77%